2009
DOI: 10.1542/peds.2008-3007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Multimicronutrient Supplementation on the Mental Development of Infants in Rural Western China: Follow-up Evaluation of a Double-Blind, Randomized, Controlled Trial

Abstract: Compared with iron and folic acid supplementation, the administration of multimicronutrients to pregnant women improved the mental development of their children at 1 year of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 21 publications
5
103
1
Order By: Relevance
“…There were no differences between children at 3 and 6 months, but at 12 months, children of mothers who had received MMNs had a higher mental development index score by 1.22 (compared with IFA) and 1.00 (compared with folic acid alone) ( p = 0.02). There were no effects on motor development [25] .…”
Section: Biological Effects Child Engagement Cognition Nutritionmentioning
confidence: 81%
“…There were no differences between children at 3 and 6 months, but at 12 months, children of mothers who had received MMNs had a higher mental development index score by 1.22 (compared with IFA) and 1.00 (compared with folic acid alone) ( p = 0.02). There were no effects on motor development [25] .…”
Section: Biological Effects Child Engagement Cognition Nutritionmentioning
confidence: 81%
“…This review found some evidence that multivitamin and mineral supplementation might positively influence certain aspects of brain development in children (Leung et al, 2011). The review included six trials on multiple-micronutrient supplementations conducted in Peru, rural Taiwan, Tanzania (on HIV infected mothers), and in rural China, Indonesia and Bangladesh, where mothers were poorly nourished (Joos et al, 1983;Schmidt et al, 2004;McGrath et al, 2006;Tofail et al, 2008;Li et al, 2009;Caulfield et al, 2010). A very recent randomized controlled trial in Indonesia found that multiple micronutrient supplementation in undernourished pregnant mothers resulted in improved motor development, visual attention and spatial ability in pre-schoolers (Prado et al, 2012).…”
Section: Multivitamin and Mineral Supplementationmentioning
confidence: 99%
“…We expect this to change. For example, Li et al (2009) analyze the effects of a double blind RCT that provided multi-micronutrient supplementation to several thousand pregnant women in rural China on measures of offspring mental and psychomotor development at up to age 1. Similarly, Vaidya et al (2008) implemented an RCT in Nepal to identify the effects of iron or folic acid supplementation during the prenatal period on various measures of childhood size, illness and blood pressure.…”
Section: Random Assignmentmentioning
confidence: 99%